2014
DOI: 10.2166/wst.2014.113
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of tunnel wash water and implications for its disposal

Abstract: The use of road tunnels in urban areas creates water pollution problems, since the tunnels must be frequently cleaned for traffic safety reasons. The washing generates extensive volumes of highly polluted water, for example, more than fivefold higher concentrations of suspended solids compared to highway runoff. The pollutants in the wash water have an affinity for particulate material, so sedimentation should be a viable treatment option. In this study, 12 in situ sedimentation trials were carried out on tunn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…zinc, copper, cadmium, nickel) and organic pollutants (e.g. polycyclic aromatic hydrocarbons, organophosphates, octylphenols, phthalates) (Grung et al 2017;Hallberg et al 2014;Meland et al 2010a, b;Meland and Rødland 2018). Road runoff has received renewed interest in recent years due to the presence of particles with polymer components; it has been identified as one of the largest sources of microplastic particles in the environment (Baensch-Baltruschat et al 2020;Kole et al 2017;Wagner et al 2018).…”
Section: Roadsmentioning
confidence: 99%
See 1 more Smart Citation
“…zinc, copper, cadmium, nickel) and organic pollutants (e.g. polycyclic aromatic hydrocarbons, organophosphates, octylphenols, phthalates) (Grung et al 2017;Hallberg et al 2014;Meland et al 2010a, b;Meland and Rødland 2018). Road runoff has received renewed interest in recent years due to the presence of particles with polymer components; it has been identified as one of the largest sources of microplastic particles in the environment (Baensch-Baltruschat et al 2020;Kole et al 2017;Wagner et al 2018).…”
Section: Roadsmentioning
confidence: 99%
“…Only a small fraction of these tunnels receives any kind of treatment of the tunnel drainage water, and most release the runoff directly into a water recipient (Rødland and Helgadottir 2018). Several studies have documented high levels of particulate matter in tunnel wash water (Hallberg et al 2014;Meland et al 2010a, b;Meland and Rødland 2018); however, there are very few that investigate concentrations of TWP or other microplastics in this matrix. It is expected that tunnel wash waters may be highly enriched in RAMP.…”
Section: Road Runoffmentioning
confidence: 99%
“…Total particle concentrations have been reported for a range of environmental samples, such as roadside snow (5-12,700 mg/L: Moghadas et al (2015), Viklander (1999), tunnel wash water (8-31,000 mg/L, Meland and Rødland (2018), Hallberg et al (2014))) and sedimentation pond effluent (<15 mg/L, Hallberg et al (2014)). Compared to previous studies, the total particle concentrations found for the roadside snow in this study are significantly higher, from 1800 to 355,000 mg/L in meltwater and 6340 to 2,810,000 mg/m 2 .…”
Section: Total Particle Concentrationsmentioning
confidence: 99%
“…The efficiency of the different basins as is not stated and may differ. Most basins are built for road runoff, and not for tunnels, even though tunnels are considered a hot-spot for road-related pollution (Grung et al, 2017;Hallberg et al, 2014;Meland & Rødland, 2018;Roseth & Meland, 2006;Åstebøl et al, 2011). Norway has in total 1229 tunnels registered in Vegkart, with more under construction and planning.…”
Section: Water Treatment Facilitiesmentioning
confidence: 99%